High serum leptin levels are associated with central arterial stiffness in geriatric patients on hemodialysis - Chiu-Huang Kuo; Yu-Li Lin; Chih-Hsien Wang; Yu-Hsien Lai; Ru-Jiang Syu; Bang-Gee Hsu (Tzu Chi Medical Journal)
Objective: Central arterial stiffness predicts cardiovascular (CV) mortality in hemodialysis (HD) patients. The aging process transforms lipid distribution and thus alters adipokine secretion. The harmful effects of leptin on CV events may change in the elderly. The purpose of this study was to investigate the relationship between leptin and central arterial stiffness markers through carotid–femoral pulse wave velocity (cfPWV) in geriatric HD patients. Materials and Methods: Patients over 65 years old on chronic HD were recruited. Blood samples were collected, and the cfPWV was measured with the SphygmoCor system. The patients with cfPWV values >10 m/s were defined as the high arterial stiffness group. Results: In total, 30 (51.7%) of the 58 geriatric patients on chronic HD in this study were in the high arterial stiffness group. The high arterial stiffness group had higher rates of diabetes mellitus (P = 0.019), hypertension (P = 0.019), and higher systolic blood pressure (P = 0.018), pulse pressure (P = 0.019), body mass index (P = 0.018), serum leptin levels (P = 0.008), and hemoglobin levels (P = 0.040) than those in the low arterial stiffness group. Multivariable forward stepwise linear regression analysis showed logarithmically transformed leptin (log-leptin, β =0.408, adjusted R2 change = 0.164; P = 0.001) and diabetes (β =0.312, adjusted R2 change = 0.085; P = 0.009) were associated with cfPWV values in geriatric HD patients. Moreover, an increased serum leptin level (odds ratio: 1.053; 95% confidence interval: 1.007–1.100; P = 0.023) was an independent factor for central arterial stiffness among geriatric HD patients after multivariate logistic regression analysis. Conclusion: In this study, a higher serum leptin level was correlated with central arterial stiffness in geriatric HD patients.